Determination and evaluation of the factors of outsourcing logistics - Jarzemskis, Andrius (Transport, 2006)
This paper focuses on the determination and evaluation of the factors of logistic outsourcing. Many authors usually talk about logistics service outsourcing and its reasons and benefits as well, but if some functions of the service are not outsourced, we can not really entitle “outsourcing” as the whole service providing. In logistics activity if one or several functions are outsourced it is not always possible to entitle “logistics outsourcing”. In this paper outsourcing logistics criteria are described. The results of the survey among traders in Lithuania of outsourcing logistics are presented as well. First Published Online: 27 Oct 2010